Psychology of interactions between units and subunits for emergency situations and mass media problem of algorithmization - Kremen’ Маркс; Gerasimchik Александр; Bogdanovich Алексей; Sergeev Всеволод; Novitskiy Виталий (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2016)
Emergencies occur mostly unpredictably and pass stochastically. Their development differs so much from “ordinary” everyday practice. Under such conditions there is a growing temptation to eliminate the uncertainty by regulation of information flows and algorithmization of actions of authorized services of MES in the field of interaction with mass media. However the relations in crises communicative media do not endure simple schemes and naïve behaviour models. The problem of applicability of algorithmization approaches in order to obtain controlled media-psychological effects is discussed in this article.